Kontribusi Stres Kerja Gaya Kepemimpinan Kepala Sekolah Dan Komitmen Organisasi Terhadap Kinerja Guru Man Kabupaten Sragen - Rusdiyanto, Rusdiyanto, Prof. Dr. Budi Murtiyasa, M.Kom, Dr. Suyatmini, M.Si (2016)
ABSTRACT Rusdiyanto. Q 100 140 050. Contributions Stress Work, Leadership Style, Principal, Organizational Commitment To Performance And Teacher MAN Sragen. Graduate program. Muhammadiyah University of Surakarta. 2016. The purpose of this study is to analyze and determine (1) the simultaneous contribution from the stress of work, school leadership style and organizational commitment on teacher performance MAN in Sragen. (2) a partial contribution from the stress of work, school leadership style and organizational commitment on teacher performance in Sragen MAN. This study will be conducted throughout the MAN in Sragen totaling 3 Schools namely Sragen MAN 1, MAN 2 Sragen, and MAN 3 Sragen. The population of as many as 121 teachers. The research sample of 80 teachers with proportional random sampling technique sampling. Data collection techniques using questionnaires and documentation study. Data analysis techniques with multiple regression analysis. The results of this study indicate that the value of F arithmetic amounted to 30.427 with a significant level of 0.000 (α : 0.05) and value R2 obtained figures for 0.546. This proves that the stress of work, school leadership style and organizational commitment simultaneously have a positive and significant contribution to the performance of teachers in MAN Sragen with a contribution of 54.6%. Job stress variable positive and significant effect on the performance of teachers in MAN Sragen. Contributions of work stress on teacher performance in Sragen regency MAN amounted to 31.26%. This is indicated by the value t count 6,546 with significant value of 0.000 (α : 0.05) and value of the effective contribution of 31.26%. Principal's leadership style variable positive and significant impact on teacher performance in MAN Sragen. Contributions of Principal's leadership style on teacher performance in Sragen regency MAN amounted to 11.62%. This is indicated by the value t count 3,108 with significant value of 0.003 (α : 0.05) and value of the effective contribution of 11.62%. Organizational commitment variable positive and significant impact on teacher performance in MAN Sragen. Contributions of organizational commitment on teacher performance in Sragen regency MAN amounted to 11.70%. This is indicated by the value t count 2,428 with significant value of 0.018 (α : 0.05) and value of the effective contribution of 11.70%. Keywords: teacher's performance, job stress, principal leadership styles, organizational commitment